Zhongguo haoren - Dao, er deng (Taiyuan : Shanxi People's Publishing House, 2017)
The book is divided into four parts, including <Why don't I like dogs> <Why can't I make a joke with a farmer> <Home schoolchildren> <Sima Xiangru: Rabbit corner bow and arrowless ghost> <Nothing and wine reading Lisao> <People's heart Only the dangerous> <Wu Sangui's letter> <Distorted Fengfang> and other essays.
In simplified Chinese script.
Keywords: Chinese literature